Methodology of Game Activities in the Child Protection Strategy (Sport for Protection): Experience of International Humanitarian Initiatives in the Education System - Oleksandra Tsybanyuk (Pedagogical Discourse, 2026)
The article provides a theoretical substantiation and reveals the content of the «Sport for Protection» game methodology as a systemic instrument for implementing international humanitarian standards in the modern educational space. The study aims to substantiate and reveal the pedagogical potential of the «Sport for Protection» methodology for ensuring the psychosocial protection and rehabilitation of youth in crisis conditions. A complex of complementary research methods was used: analysis and synthesis of the «Sport for Protection Toolkit» conceptual package; methodological modeling of the trainer training structure and game session stages; content analysis of specialized manuals («Coach2Coach Programme Book», «Learner’s Guide to Coach2Coach»); and expert interpretation of «Right to Play» annual reports to determine success criteria for sport leagues and community engagement. Its strategic mission is based on integrating innovative game methodologies into social inclusion processes and empowering children in conflict zones or regions with critical poverty. The research highlights that the pedagogical strategy focuses on leveling educational and humanitarian gaps by developing the resilience of the younger generation. The «Refugee Coach2Coach» program implements a cascade training model where professional international instructors prepare local Master Trainers from among refugees, who then train local volunteers. The integrated approach to child development is realized through the «5 Rings» program (Mind, Spirit, Body, Health, Peace), where each ring corresponds to specific games and exercises. A crucial finding is the systematization of the game toolkit into three functional groups: 1) social cohesion and inclusion; 2) psychosocial well-being and stress reduction; 3) life skills and trust. Central to the methodology is the three-stage RCA (Reflect – Connect – Apply) feedback method, which transforms physical activity into a cognitive experience, allowing participants to extrapolate game skills to real-life challenges.